86.0k views
2 votes
2x+3

7. Find each value if f(x)=x²-2x-8 and g(x)=-2x+1
(b) f(-3d)
(a) f(3)
(d) g(5)
(e) g(3x)
(e) f(2a-1)
(1) g(-4a+8)

2x+3 7. Find each value if f(x)=x²-2x-8 and g(x)=-2x+1 (b) f(-3d) (a) f(3) (d) g(5) (e-example-1
User Subbul
by
5.7k points

1 Answer

7 votes

Answer:

Explanation:

a. f(-3d) = (-3d)^2 - 2(-3d) - 8 = 9d^2 + 6d - 8

b. f(3) = (3)^2 - 2(3) - 8 = 9 - 8 - 8 = 1 - 8 = -7

c. f(2a - 1) = (2a - 1)^2 - 2(2a - 1) - 8 = 4a^2 - 4a + 1 -4a + 2 - 8 = 4a^2 - 8a - 5

d. g(5)= (2(5)+3)/(5^2 -2(5) + 1) = (10 + 3)/(25 - 10 + 1)= 13/15+1= 13/16

e. g(3x)= (2(3x) + 3))/((3x)^2 - 2(3x) + 1))= (6x + 3)/(9x^2 - 6x + 1)

f. g(-4a + 8) = (2(-4a + 8)) + 3/(-4a + 8)^2 - 2(-4a +8) +1))

(-8a + 16 + 3)/(16a^2 - 32a + 64 + 8a - 16 + 1)

(-8a + 19)/(16a^2 - 24a + 49)

User Torno
by
5.1k points